Investigating the Effect of Ozone on the Biodegradability of Distillery Wastewater - Sigge, G.O.; Green, J.; du Plessis, K.R.; Britz, T.J. (South African Journal of Enology and Viticulture, 2016)
The effect of ozonation on wine distillery wastewater was investigated firstly by monitoring the effect of ozonation on the composition of the wastewater and, secondly, by investigating its effect on the biodegradability of the wastewater. An average COD reduction of 271 mg COD.g O3 -1 was found for wastewater from a distillery pond system. Stable microbial populations, which are found in upflow anaerobic sludge blanket (UASB) granules, were used to determine the toxic effect of wastewater on microbial activity. Granule activity was measured in terms of the rate of biogas and methane production, as well as cumulative biogas volume. Low ozone doses (200 to 400 mg O3.L-1) increased granule activity in terms of biogas, methane production, and cumulative gas volumes. Distillery wastewater reduced the activity of granules, most likely due to the presence of polyphenols and other recalcitrant compounds in the distillery wastewater.